Evaluating the Effectiveness of Mindfulness-Based Interventions in Incarcerated Populations: A Meta-Analysis - Per, Megan (Criminal justice and behavior, 2020)
A growing body of research supports the use of mindfulness-based interventions (MBIs) in incarcerated populations; however, treatment effectiveness remains unclear. This meta-analysis of 22 studies (N = 2,265, 75% male) quantified the effectiveness of MBIs in incarcerated populations on key psychological outcomes and criminogenic needs. Results from pre-post studies indicated MBIs had a small to moderate effect on all outcomes, but this was not supported by controlled studies. Studies with older participants, more females, and longer treatment length demonstrated slightly greater effects. Results from pre-post analyses demonstrated significant reductions in psychological outcomes (depression, anxiety, and stress) and criminogenic needs (impulsivity, self-dysregulation, anger, substance use behavior, and attitude). However, only depression and anxiety were significantly reduced in controlled studies. Although findings offer preliminary support of the efficacy of MBIs in targeting psychological health in incarcerated populations, further controlled studies are required to examine criminogenic outcomes and recidivism rates after treatment.